Burden of type 1 diabetes mellitus in the North Africa and Middle East Region, 1990–2019; findings from the global burden of disease study. (June 2022) - Esmaeili, Shahnaz; Saeedi Moghaddam, Sahar; Namazi, Nazli; Bandarian, Fatemeh; Esfahani, Zahra; Peimani, Maryam; Shahin, Sarvenaz; Nasli-Esfahani, Ensieh; Akbarzadeh, Isa; Ghanbari, Ali; Rezaei, Negar; Rezaei, Nazila; et al.
Abstract: Aims: We aimed to report the burden of type 1 diabetes mellitus (T1DM) in the North Africa and Middle East region and its 21 countries from 1990 to 2019. Methods: Information related to incidence, prevalence, mortality, disability-adjusted life-years (DALYs), and years lived with disability (YLDs) of T1DM was acquired from the 2019 Global Burden of Disease study. The burden was estimated by sex, age groups, and socio-demographic index (SDI) in 21 countries. Results: Over the past 30 years, regional incidence, prevalence, mortality, and DALYs of T1DM increase by 188.7%, 304.8%, 43.7%, and 71.6%, respectively. While the age-standardized incidence and prevalence rates increased by 84% and 91%, the mortality and DALYs rates decreased by 34% and 13%. During these years, the contribution of YLDs to total DALYs increased considerably (from 17% to 42%). The highest increase in the incidence and prevalence rates occurred in high SDI countries. Moreover, the Mortality to Incidence Ratio (MIR) decreased in the region countries. Conclusions: Despite progress made in diabetes care, there is a persistently increasing burden of T1DM in the region countries. This indicates that T1DM is still one of the major health challenges in the region countries, especially in high SDI Arab countries.